Efforts to Increase Growth and Flowering of (Impatiens hawkeri Bull) Through Eco-Enzyme Application and Goat Fertilizer Dosage - Hidayah, Eva Mazidatul; sitawati, Sitawati sitawati (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2024)
Impatiens New Guinea (Impatiens hawkeri Bull) is a type of plant that is classified as an ornamental horticultural plant that is cultivated because it has economic value, which is cultivated as an ornamental plant dan herbaceous plant and is able to survive in a hot dan high temperature environment. The level of productivity of new guinea plants in Indonesia has decreased due to the narrowing of land area, pests and diseases that attack sub-optimal soil fertility, fertilization that is not in accordance with the dosage and dosage, resulting in decreased flower productivity. To maintain the productivity of new guinea plant flowers, it is necessary to apply the use of eco-enzyme applications and the provision of goat manure as a substitute for inorganic fertilizers. The study used a completely Factorial Randomized Block Design (Factorial RBD) with 2 factors, namely the concentration of eco-enzyme dan the dose of goat manure with 3 replications. The results showed that there was an interaction between the treatment of eco-enzyme concentration and dose of goat manure on the parameters of plant length, number of leaves, chlorophyll index, number of branches, flower emergence time, dan total flowers per plant. The application of concentration dan eco-enzyme 5 ml l-1 and 50% manure was able to increase the number of flowers by 16%. The addition of eco-enzyme 10 ml l-1 and 100% goat manure increased the number of flowers by 56% dan accelerated the time of flower emergence to 23 days after planting.